2015
DOI: 10.11114/smc.v3i2.970
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cyberstalking

Abstract: To access the diversity of the population who define themselves as having been cyberstalked and to assess the levels of anxiety and trauma that victims reported. Participants who were self-defined cyberstalking victims (N = 353) were asked to complete an online survey, which consisted of items relating to the experience of offline harassment and cyberstalking, general anxiety and post-traumatic stress symptoms. Participants were also asked to report on the type of relationship they had with the harasser, chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…With regard to social consequences, the only difference was that traditional stalking was associated more with changes to the victim's employment status and social routines whereas cyberstalking was more strongly associated with loss of significant relationships. More recently, using standardized measures of anxiety and PTSD, Short, Guppy, Hart, and Barnes (2015) reported that both traditional stalking and cyberstalking victims experience comparable elevated levels of psychological distress as a consequence of the ordeal. In line with this, when Dreßing, Bailer, Anders, Wagner, and Gallas (2014) presented users of a German social networking site with a list of psychosomatic and psychosocial symptoms, over half of the individuals who had experienced cyberstalking reported anger, helplessness, and anxiety.…”
mentioning
confidence: 99%
“…With regard to social consequences, the only difference was that traditional stalking was associated more with changes to the victim's employment status and social routines whereas cyberstalking was more strongly associated with loss of significant relationships. More recently, using standardized measures of anxiety and PTSD, Short, Guppy, Hart, and Barnes (2015) reported that both traditional stalking and cyberstalking victims experience comparable elevated levels of psychological distress as a consequence of the ordeal. In line with this, when Dreßing, Bailer, Anders, Wagner, and Gallas (2014) presented users of a German social networking site with a list of psychosomatic and psychosocial symptoms, over half of the individuals who had experienced cyberstalking reported anger, helplessness, and anxiety.…”
mentioning
confidence: 99%
“…While most established research has focused on conventional crimes such as burglary, sexual and violent offences, more recently the effects of online crime such as cyber abuse 3 have been studied (Sheridan and Grant, 2007;Hensler-McGinnis, 2008;Dreßing et al, 2014;Nobles et al, 2014;Short et al, 2014;Short et al, 2015;Worsley et al, 2016;Fissel, 2018;Fissel and Reyns, 2019). Research suggests that, much like the victims of conventional crimes, victims of cybercrimes such as cyber abuse experience a variety of negative effects including persistent psychological impairment and issues of personal insecurities (Parsons-Pollard and Moriarty, 2009;Dreßing et al, 2014;Nobles et al, 2014).…”
Section: The Effect Of Offence Type On Victim Impactmentioning
confidence: 99%
“…Victims of cyberstalking were also more likely to report adopting self-protective behaviours compared with victims of offline stalking. Short et al (2015) compared the victim impact from offline and online harassment and found that both could result in high levels of psychological distress comparable to the effects of post-traumatic stress disorder. In a different setting, Hensler-McGinnis (2008) examined a sample of university students and found that cyberstalking victimization was significantly associated with trauma and impairment in academic/career functioning.…”
Section: The Effect Of Offence Type On Victim Impactmentioning
confidence: 99%
“…Reference [10] showed that female victims of cyberstalking (stalking by means of email, text messages or the internet) made up 4% of all 18-to 29-year-old women in the EU. Short and colleagues [11] analyzed data from 353 self-defined victims of stalking and found that the majority of the victims were female (240) between the ages of 20 and 39 (58.6%). In a previous study conducted by two of the authors of this work [12,13] that involved 107 young adult self-declared victims of cyberstalking, the findings showed that the victims were mainly females (61%).…”
Section: Introductionmentioning
confidence: 99%